2014
DOI: 10.1021/sc5001435
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II,III)–Polyphenol Complex Nanoparticles Derived from Green Tea with Remarkable Ecotoxicological Impact

Abstract: There are several green methods available to synthesize iron-based nanoparticles using different bio-based reducing agents. Although their useful properties in degradation of organic dyes, chlorinated organics, or arsenic have been described earlier, their characterization has been ambiguous, and further research is needed in this area. Synthesis and characterization details on iron-based nanoparticles produced by green tea extract are described in detail; characterization was carried out by transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 40 publications
5
69
1
Order By: Relevance
“…Hydroxyl groups from sugars and phenolics can affect the reduction of metal salts including also vitamins [35][36][37][38][39][40][41][42]. Aerial parts of Sorbaria sorbifolia are known to contain a variety of polyphenols, flavonoids and glycosides [23][24][25]; glycosides are non-reducing sugars, but polyphenols and flavonoids are known …”
Section: Possible Mechanism For Reduction Efficiency Of Plementioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyl groups from sugars and phenolics can affect the reduction of metal salts including also vitamins [35][36][37][38][39][40][41][42]. Aerial parts of Sorbaria sorbifolia are known to contain a variety of polyphenols, flavonoids and glycosides [23][24][25]; glycosides are non-reducing sugars, but polyphenols and flavonoids are known …”
Section: Possible Mechanism For Reduction Efficiency Of Plementioning
confidence: 99%
“…Hydroxyl groups from sugars and phenolics can affect the reduction of metal salts including also vitamins [35][36][37][38][39][40][41][42]. Aerial parts of Sorbaria sorbifolia are known to contain a variety of polyphenols, flavonoids and glycosides [23][24][25]; glycosides are non-reducing sugars, but polyphenols and flavonoids are known antioxidants that serve as reducing agents [36][37][38][39] and are thus most likely responsible for the reduction of Cr(VI) to Cr(III) using 'greener' PLE as a reductant. A schematic presentation delineates the reduction mechanism (Figure 8a-c); captured image for the gradual conversion of carcinogenic Cr(VI) into nontoxic Cr(III) is shown in Figure 8e. antioxidants that serve as reducing agents [36][37][38][39] and are thus most likely responsible for the reduction of Cr(VI) to Cr(III) using 'greener' PLE as a reductant.…”
Section: Possible Mechanism For Reduction Efficiency Of Plementioning
confidence: 99%
“…Additionally, peaks from 210 to 260 nm are seen in the two analyzed samples, and it is suggested that they resemble the presence of polyphenols. Markova et al [25] biosynthesized nanoparticles with green tea leaves and compared with nanoparticles synthesized with sodium borohydride. Nanoparticles prepared with green tea leaves showed peaks at 210, 220, and 270 n, whereas in the inorganic samples (nanoparticles with sodium borohydride), these peaks do not show up.…”
Section: Characterization Of Multicomponent Nanoparticlesmentioning
confidence: 99%
“…Low-temperature measurements, especially in materials research, bring on many positives, i.e., characterizing the superparamagnetic materials in magnetically ordered state (below the blocking temperature), resolving spectral components or analyzing the liquid samples in a frozen state, etc. [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…A cryostat operating at the stable temperature of liquid nitrogen, i.e., 77 K, offers a possible way how to easily perform low temperature analyses, moreover without extra vibrations. This system can be used in cases when it is necessary to stop the chemical reaction at a given time [3]. Additionally, the cryostat can be equipped with the temperature control system with the heater, which allows achieving a higher temperature than the temperatures of the cryogen liquids.…”
Section: Introductionmentioning
confidence: 99%